Recent progress and future prospects for mechanized harvesting of fruit crops with shaking systems - Pu, Yingjun; Wang, Shuming; Yang, Fuzeng; Ehsani, Reza; Zhao, Lijun; Li, Chengsong; Xie, Shouyong; Yang, Mingjin (International Journal of Agricultural and Biological Engineering, 2023)
Mechanized harvesting technologies with shaking systems for fruit industry have been widely investigated and significantly developed over the past several decades which were presented by a large amount of literature. This paper reviews the research and development progress of mechanized harvesting of fruits systematically with a focus on the theoretical study, fruit crop variety, shaking system categories, abscission chemical agents, and their actual applications. Based on the comprehensive review, mechanized harvesting systems for different fruit crops appear multifarious shaking modes with various vibratory mechanisms and structural dimensions. Major advantages in the development of fruit mechanical harvesting with effective vibratory patterns and catching frames provide a series of economic and agronomic benefits, such as reducing labor costs, promoting standardized planting, and increasing productivity. However, fruit injury and tree damage are the main reasons why mechanical shaking systems are rarely used for fresh fruit harvesting because of tenderness and frangibility of the fruit crops. Therefore, more efforts should be concentrated on the innovative shake-and-catch system with suitable frequency and amplitude to achieve low fruit damage or even nondestructive harvesting for fresh fruit market. This overview summarized the advantages and bottlenecks of these shaking systems for fruit harvesting and proposed the challenges and some constructive prospective viewpoints aimed at the major issues of mechanical harvesting techniques. In addition, employing sorting technologies to classify the postharvest fruits provide a new direction for the further development of mechanized harvesting in high-value fruit crops, as well as bring more benefits to growers and increase their interest in equipment investment on the mechanical shaking harvester for the fruit industry.Keywords: fruit crop, mechanized harvesting, shaking system, fruit injury, postharvest classificationDOI: 10.25165/j.ijabe.20231601.7954Citation: Pu Y J, Wang S M, Yang F Z, Ehsani R, Zhao L J, Li C S, et al. Recent progress and future prospects for mechanized harvesting of fruit crops with shaking systems. Int J Agric & Biol Eng, 2023; 16(1): 1–13.